Alpha-galactosylceramide enhances mucosal immunity to oral whole-cell cholera vaccines - Lavelle, Edward; Mc Entee, Craig (My University, 2019)
Cholera is a severe diarrheal disease caused by the bacterium Vibrio cholerae (V. cholerae) that results in 3–4 million cases globally with 100,000–150,000 deaths reported annually. Mostly confined to developing nations, current strategies to control the spread of cholera include the provision of safe drinking water and improved sanitation and hygiene, ideally in conjunction with oral vaccination. However, difficulties associated with the costs and logistics of these strategies have hampered their widespread implementation. Specific challenges pertaining to oral cholera vaccines (OCVs) include a lack of safe and effective adjuvants to further enhance gut immune responses, the complex and costly multicomponent vaccine manufacturing, limitations of conventional liquid formulation and the lack of an integrated delivery platform. Herein we describe the use of the orally active adjuvant α-Galactosylceramide (α-GalCer) to strongly enhance intestinal bacterium- and toxin-specific IgA responses to the OCV, Dukoral®in C57BL/6 and BALB/c mice. We further demonstrate the mucosal immunogenicity of a novel multi-antigen, single-component whole-cell killed V. cholerae strain and the enhancement of its immunogenicity by adding α-GalCer. Finally, we report that combining these components and recombinant cholera toxin B subunit in the SmPill®minisphere delivery system induced strong intestinal and systemic antigen-specific antibody responses.
PUBLISHED
cited By 0
Keywords: Vibrio cholerae; Cholera; Oral cholera vaccines (OCVs; α-Galactosylceramide (α-GalCer); Mucosal Immunity